Benarkah Gender Mempengaruhi Hasil Belajar Bahasa Arab - Wa Muna; Suparno Suparno (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
His study aims to prove whether there is an effect of gender on Arabic learning outcomes at the elementary school level. The research used a quantitative approach, with the research subjects being students in grades II and IV of Asy-Syafi'i Integrated Islamic Elementary School (SDIT) in the academic year 2023-2024, with a total sample size of 54 students. The data were analyzed using an independent sample t-test. The results of the analysis show that there is no significant difference in Arabic learning outcomes based on gender.